State-of-the-art monitoring in treatment of dengue shock syndrome: a case series. (December 2016) - Moulton, Steven; Mulligan, Jane; Srikiatkhachorn, Anon; Kalayanarooj, Siripen; Grudic, Greg; Green, Sharone; Gibbons, Robert; Muniz, Gary; Hinojosa-Laborde, Carmen; Rothman, Alan; Thomas, Stephen; Convertino, Victor
Abstract Background Early recognition and treatment of circulatory volume loss is essential in the clinical management of dengue viral infection. We hypothesized that a novel computational algorithm, originally developed for noninvasive monitoring of blood loss in combat casualties, could: (1) indicate the central volume status of children with dengue during the early stages of "shock"; and (2) track fluid resuscitation status. Methods Continuous noninvasive photoplethysmographic waveforms were collected over a 5-month period from three children of Thai ethnicity with clinical suspicion of dengue. Waveform data were processed by the algorithm to calculate each child's Compensatory Reserve Index, where 1 represents supine normovolemia and 0 represents the circulatory volume at which hemodynamic decompensation occurs. Values between 1 and 0 indicate the proportion of reserve remaining before hemodynamic decompensation. Results This case report describes a 7-year-old Thai boy, another 7-year-old Thai boy, and a 9-year-old Thai boy who exhibited signs and symptoms of dengue shock syndrome; all the children had secondary dengue virus infections, documented by serology and reverse transcriptase polymerase chain reaction. The three boys experienced substantial plasma leakage demonstrated by pleural effusion index >25, ascites, and >20 % hemoconcentration. They received fluid administered intravenously; one received a blood transfusion. All three boys showed a significantly low initial Compensatory Reserve Index (≥0.20), indicating a clinical diagnosis of "near shock". Following 5 days with fluid resuscitation treatment, their Compensatory Reserve Index increased towards "normovolemia" (that is, Compensatory Reserve Index >0.75). Conclusions The results from these cases demonstrate a new variation in the diagnostic capability to manage patients with dengue shock syndrome. The findings shed new light on a method that can avoid possible adverse effects of shock by noninvasive measurement of a patient's compensatory reserve rather than standard vital signs or invasive diagnostic methods.